Acknowledging tissue donation: Human cadaveric specimens in musculoskeletal research. Issue 1 (19th November 2015) - Winkelmann, Andreas; Heinze, Anne‐Kathrin; Hendrix, Sven
Abstract : Human cadaveric specimens are an important resource for research, particularly in biomechanical studies, but their use also raises ethical questions and cannot simply be taken for granted. It was asked how much information authors publishing musculoskeletal research actually give about such specimens and about how they were acquired. The aim was to formulate recommendations on how this reporting might be improved. Relevant articles published between 2009 and 2012 in four North American or European journals were scanned for information regarding the characteristics of the human specimens used, their institutional source and the ethical or legal context of their acquisition. While the majority of articles report biological characteristics of specimens (sex, age at death, preservation method), only 40% of articles refer to body donation, only 23% report the institution that provided specimens, and only 17% refer to some kind of formalized approval of their research. There were regional and journal‐to‐journal differences. No standard for reporting studies involving human specimens could be detected. It is suggested that such a standard be developed by researchers and editors. Information on the source of specimens and on the ethical or legal basis should be regularly reported to acknowledge this unique research resource and to preserve the good relationship between researchers and the communities, that provide the required specimens by body donation and upon which researchers depend. Clin. Anat. 29:65–69, 2016. © 2015 Wiley Periodicals, Inc.